2014
DOI: 10.1142/s1464333214500227
|View full text |Cite
|
Sign up to set email alerts
|

Current State of the Sea System in Brazil: A Comparative Study

Abstract: After the first applications in the early 1990's, the practice of SEA in Brazil has been going through a slow, but important evolution. In this paper we elaborate on the main aspects of this evolution, based on the findings of a comparative study that put the practice of SEA in different contexts into perspective. SEA systems considered included consolidated (UK, Spain and Portugal) and unconsolidated (South Africa, Mexico, Angola and Mozambique) systems. The Brazilian system is characterised by a disperse str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
11

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 29 publications
0
15
0
11
Order By: Relevance
“…In Brazil, the first attempt to institutionalize the SEA was in São As for application cases, there is a record of some SEA experience in the country: ten cases are described by Teixeira (2008); two SEAs applied to the tourism sector were studied by Lemos (2011);Malvestio and Montaño (2013) identified 35 SEAs in the energy sector; Margato and Sánchez (2014) raised 24 SEAs; Oberling, La Rovere and Silva (2013), studied 21 SEAs; da Silva, Selig and Van Bellen (2014), raised 32 SEAs; and finally Montaño et al (2014), gathered knowledge of about 40 EIAs. Despite these cases, the lack of a Brazilian regulatory framework on SEA and the gap in the defining the implementation and analysis role result in the inexistence of an official repository of SEA reports developed in Brazil.…”
Section: Strategic Environmental Assessment and Its Role In Planningmentioning
confidence: 99%
See 1 more Smart Citation
“…In Brazil, the first attempt to institutionalize the SEA was in São As for application cases, there is a record of some SEA experience in the country: ten cases are described by Teixeira (2008); two SEAs applied to the tourism sector were studied by Lemos (2011);Malvestio and Montaño (2013) identified 35 SEAs in the energy sector; Margato and Sánchez (2014) raised 24 SEAs; Oberling, La Rovere and Silva (2013), studied 21 SEAs; da Silva, Selig and Van Bellen (2014), raised 32 SEAs; and finally Montaño et al (2014), gathered knowledge of about 40 EIAs. Despite these cases, the lack of a Brazilian regulatory framework on SEA and the gap in the defining the implementation and analysis role result in the inexistence of an official repository of SEA reports developed in Brazil.…”
Section: Strategic Environmental Assessment and Its Role In Planningmentioning
confidence: 99%
“…The study of procedural effectiveness of SEA practice in Brazil driven by Montaño et al (2014) showed that, although more than half of the cases have adopted procedures used in the literature and in international guidelines, the instrument has to be improved in Brazil, even regarding its procedural aspects. Previous research highlighted the lack of consistency in the Brazilian SEA procedures and the need to improve the current system emphasizing the urgency of the discussion of methodologies, approaches and ways for implementing and improving instrument practice (SÁNCHEZ; SILVA-SÁNCHEZ, 2008;PELLIN et al, 2011;MONTAÑO, 2013).…”
Section: Strategic Environmental Assessment and Its Role In Planningmentioning
confidence: 99%
“…Ao mesmo tempo, o fomento a boas práticas de AAE no Brasil aparece em recentes pesquisas nacionais (SÁNCHEZ & SILVA-SÁNCHEZ, 2008;PELLIN et al, 2011), como uma forma de garantir rigor técnico, provisionando orientação procedimental e aprimoramento do sistema de AAE brasileiro (MONTAÑO et al, 2014), como, por exemplo, na proposição de Gallardo et al (2016), acerca de um roteiro de AAE para subsidiar o planejamento da expansão da cana-de-açúcar.…”
Section: Introductionunclassified
“…As noted by Montaño et al (2014) the number of studies assessing SEA systems is increasing, allowing inferences about the importance of the context in SEA. The common items between the different approaches are (i) legal basis for SEA application and guidance tools; (ii) existing process and procedural framework (including stages of the SEA (e.g., screening, scoping, environmental assessment, public participation, follow-up) and assessment methodologies and components (assessment techniques and issues)); (iii) SEA review and influence to the decision-making (Chaker et al, 2006;Rachid and El Fadel, 2013;Therivel, 1993;Zhou and Sheate, 2009).…”
Section: Introductionmentioning
confidence: 99%